HEALTH-RELATED QUALITY OF LIFE IN THE PATIENTS WITH THE SENSORINEURAL HEARING LOSS OF PROFESSIONAL GENESIS - Дьякович, Марина Пинхасовна; Семенихин, Виктор Андреевич; Раудина, Светлана Наильевна (Medicine in Kuzbass, 2017)
Subject. Patients with sensorineural hearing loss (SNHL) of professional genesis.Objective. To reveal the features of the formation of SNHL of professional genesis and to assess its impact on the health-related quality of life (HRQL) of workers in the coal industry of Kuzbass.Methods. HRQL was studied using MOS SF-36 questionnaire with an estimation of the total physical component (PC).Main results. The peculiarities of the formation of sensorineural hearing loss of professional genesis have been revealed. The effect of sensorineural hearing loss on the health-related quality of life of workers has been assessed.Area of application. Occupational medicine, occupational pathology.Conclusions. The negative impact of the disease to a greater extent on the physical than on the mental component of HRQL of the patients is shown.
Keywords: sensorineural hearing loss of professional genesis; miners; health-related quality of life; peculiarities of the sensorineural hearing loss formation